EVALUATION OF INFORMATION PROCESSES OF MANAGEMENT OF BUSINESS ENTITIES - LUKIANOVA, VALENTYNA; POLOZOVA, VALENTYNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the study of the evaluation of information processes of management of business entities (enterprises). The purpose of the article is to substantiate the methodological approach to assessing the effectiveness of the information management process through the evaluation of information procedures of certain areas of the enterprise with subsequent practical testing of this technique. The need to assess the quality of management information processes, which determine the quality and efficiency of development and management decision-making processes and directly affect the effectiveness of the operation and efficiency of the enterprise as a whole. It is proposed to evaluate the effectiveness of information processes through the effectiveness of certain areas of activity of the business entity. In our opinion, indicators of the effectiveness of the information process of enterprise management should be formed into three groups: indicators of the financial sphere; indicators of the labor sphere; indicators of the production sphere. The effectiveness of the information management process was evaluated using data for 2018-2020 of one of the Ukrainian industrial enterprises. The forecast of separate partial indicators of an estimation is carried out, tendencies of changes of indicators are revealed. The use of the proposed methodology allowed to identify problem areas and suggest specific areas in the context of the information strategy of the enterprise to improve the efficiency of information processes in various areas of the entity. Thus, the proposed and tested method of evaluating the effectiveness of information through the effectiveness of certain areas of the enterprise allows to identify problems with the effectiveness of information procedures and identify areas of tactical change, as well as to address solutions to problems identified in developing information strategy.
Keywords: information; information process; information management process; evaluation of information management process